Cost and health effects of case management compared with outpatient clinic follow‐up in a Dutch heart failure cohort - Henk vanVoorst; Alfred Ernest Reiner Arnold (ESC Heart Failure)
Abstract Aims Heart failure reduces quality of life and life expectancy; hospital admissions are frequent and create a burden on public resources. This study aims to quantify the benefits in terms of health effects [quality‐adjusted life years (QALYs)] and costs when heart failure patients receive case management at home compared with outpatient cardiology clinic follow‐up. Methods and results A health state transition (Markov) model was written, and transition probabilities were derived from a cohort of 1114 patients and available literature. QALYs in different health states of heart failure patients were retrieved from the literature, and costs were estimated with data from the financial department of the Noordwest Ziekenhuisgroep and public cost sources. Monthly simulation cycles were repeated 60 times to generate 5 years of virtual follow‐up data. Baseline willingness to pay is assumed €50 000 per QALY. Sensitivity analyses were performed in a one‐way deterministic and a multiway probabilistic approach; the probabilistic approach used uniform and more plausible distributions of the model parameters. Case management reduced costs by €382 and increased QALYs by 0.261 for the baseline simulation; this results in a net monetary benefit of €13 428. Probabilistic sensitivity analysis based on uniform and most plausible distributions of parameters resulted in 96.2% and 83.3% of the simulations, favouring a treatment strategy of case management. Conclusions Case management is cost effective in 83.3% of the probabilistic simulations and has a tendency towards reducing costs and increasing QALYs when considering a real‐world cohort of heart failure patients in the Netherlands.